Professional development and training of preschool teachers - Radovanović, Nena B (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2019)
The aim of this paper is to point out the importance of professional development and training of preschool teachers. It derives from the view that the time in which we live brings a number of changes and challenges for all the employees in education, including preschool teachers. In order to provide an adequate response to new needs, a system of professional development and compulsory professional training is established, which is based on important program and legal documents. These documents point to the need for permanent education of educators in different fields in order to achieve higher level of quality of work with preschool aged children. The education of preschool teachers is facing many challenges, because undergraduate education can not be enough throughout entire career of preschool teacher. For this reason it is very important to develop a system of professional training, as well as concrete steps that contribute to the improvement of compulsory professional development.